Kajian Pengembangan Budidaya Ikan Kerapu dan Rumput Laut di Perairan Timur Pulau Serangan - Sari, Septi Novita; Nyoman Nurweda, I Dewa; Faiqoh, Elok; Giri Putra, I Nyoman (Journal of Marine Research and Technology, 2019)
Grouper and seaweed are Indonesian fishery export commodities. One of the regions contributing to the production of groupers and seaweed is the northern waters of Serangan, Bali. However, over the past few years, the production of groupers and seaweed in the northern waters of Serangan has decreased. With these conditions, an effort is needed to increase the production of grouper and seaweed more optimally. One of these efforts is the expansion of area for the development of grouper and seaweed aquaculture in other places, because at present in the northern waters of the attack the condition is not conducive due to the dense sea traffic activities. One place to be used as a place to develop grouper and seaweed aquaculture is the eastern waters of Serangan because it is not too busy with sea traffic activities in the region. To see the potential of the eastern waters of Serangan, it is necessary to study the physical, chemical and biological parameters of these waters. Through the study of these water parameters, it aims to find suitable locations for the development of grouper aquaculture and the development of seaweed cultivation in terms of water quality. The results showed that, in the eastern and northern waters of Serangan, are 60% and 65.21% respectively of the condition of the waters is quite suitable to support the development of grouper aquaculture. Whereas, in the eastern waters of Serangan Island, at the north and central parts, about 64.8% of the condition of the waters is quite appropriate to support the development of seaweed cultivation. Suggestions that can be given through this research is that an economic and socio-cultural review is needed in the eastern waters area of Serangan as a place for developing grouper and seaweed aquaculture.